Hubungan Pola Asuh Orang Tua dan Hasil Belajar Anak Usia 5-6 Tahun pada Masa Pembelajaran Daring di TK Al Fadholi Kota Malang - Alfi Zakiyya Chumairoh; Tomas Iriyanto; Wuri Astuti (Jurnal Dirosah Islamiyah, 2024)
Since the end of 2019, the world has been hit by the Corona Virus Disease 19 pandemic or commonly known as Covid-19. Following up on the government policy above, the Minister of Education and Culture of the Republic of Indonesia ordered that learning during the Covid-19 emergency be carried out boldly (online) or by conducting distance learning. Parents have quite a big influence on children's learning outcomes during the Covid-19 pandemic, where all learning is carried out boldly from home.Bold learning increases the intensity of meetings between children and parents, so that almost 24 hours the child will meet, be cared for and receive education from their parents. The type of parenting style applied will also influence the condition of the child and his environment when learning takes place.The aim of this research is to determine the type of parenting style applied by parents, children's learning outcomes during the pandemic and the relationship between parental parenting patterns and the learning outcomes of children aged 5-6 years during dare learning. This research uses a quantitative approach with a correlational design. The population consists of 69 children aged 5-6 years at AL Fadholi Kindergarten, Malang City. The sample in this study was all children selected as samples.The results of this research show that the correlation coefficient is 0.276, a finding that can be concluded that there is a relationship between parental parenting variables and children's overall learning outcome variables. In other words, the learning outcomes of children aged 5-6 years at Al Fadholi Kindergarten, Malang City, do not have much influence on parents' parenting patterns. Furthermore, there is a significant result (sig) of 0.022 between the parenting pattern variable and the child's overall learning outcome variable. This shows that there is a significant relationship between parenting styles and the learning outcomes of children aged 5-6 years at Al Fadholi Kindergarten, Malang City. Of the 69 parents of children aged 5-6 years, 14 people (around 20%) used an authoritarian parenting style, 42 people (around 61%) used a supportive parenting pattern, 12 people (around 17%) used a permissive parenting pattern, and 1 person (around 1%) use an unvolved parenting pattern (don't care). Based on the explanation above, it can be concluded that during the courageous learning period at Al Fadholi Kindergarten, Malang City, the learning outcomes of children aged 5-6 years were significantly correlated with parental parenting patterns which were overall authoritarian, supportive, permissive and univolved (not involved).